2011
DOI: 10.1002/j.1532-2149.2011.00018.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential patterns of opioid use: Defining persistent opioid use in a prescription database

Abstract: In the patient populations identified by the three definitions, a high rate of retention was observed, indicating that the proposed definitions can identify patients with long-term persistent use of opioids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(89 citation statements)
references
References 25 publications
3
78
0
8
Order By: Relevance
“…Although this interval is substantially longer than some reported definitions of long term opioid use, 29,30 several studies have reported that a substantial percentage of patients use opioids consistently for up to 2 years following lumbar surgery. 2,31,3234 We examined long-term opioid use as both a binary (≥365 days) and a continuous outcome.…”
Section: Methodsmentioning
confidence: 86%
“…Although this interval is substantially longer than some reported definitions of long term opioid use, 29,30 several studies have reported that a substantial percentage of patients use opioids consistently for up to 2 years following lumbar surgery. 2,31,3234 We examined long-term opioid use as both a binary (≥365 days) and a continuous outcome.…”
Section: Methodsmentioning
confidence: 86%
“…Previous studies of Nordic populations report a prevalence of heavy NSAID use of 1.5 % [18] and persistent opioid use of 1.1 % [16]. Thus, the point prevalence of persistent use of NSAIDs, opioids or paracetamol at 4 % seems reasonable.…”
Section: Prevalence and Duration Of Persistent Analgesic Usementioning
confidence: 86%
“…There have been several studies on persistent opioid use [4,[14][15][16][17], while reports on heavy use of NSAIDs [18] and self-reported regular analgesic use also exist [5,19].…”
Section: Introductionmentioning
confidence: 97%
“…7,10 The criteria are based on dispensed opioid volume and number of prescriptions during 365 days. The criteria for the wide definition of persistent opioid use are an opioid quantity > 180 DDD or 4500 OMEQ (oral morphine equivalents) during 365 days, with prescriptions in at least three of four quarters.…”
Section: Definitionsmentioning
confidence: 99%
“…[4][5][6] Depending on definition, 0.14-1.08% of Norwegians are persistent users of opioids for non-cancer pain. 7 According to the data from the Nord-Trøndelag Health Study (HUNT)3, persons with persistent opioid use experience high levels of pain in spite of opioid treatment. Even though patterns of opioid use and concomitant medication have been extensively investigated in persistent opioid users, little is known about in which ways they differ from other patients with chronic non-malignant pain and if they used their medications as prescribed.…”
mentioning
confidence: 99%